Visibility and impact of the Cuban dental scientific output, Scopus 1995-2017 - Ibraín Corrales-Reyes; Yasmany Fornaris-Cedeño; Alberto Dorta-Contreras; Josmel Pacheco-Mendoza (Universidad de Concepción., 2020)
Aim: To identify the differences between Cuban scientific research published in highly visible journals and the rest of the national dental scientific output. Materials and Methods: A bibliometric analysis was conducted using 1995-2017 data from the Scopus data-base. The following search strategy was used: country (Cuba), subject area (dentistry), publication source (Journals), article type (Original Research, Review Article). Bibliometric indicators of output, visibility, leadership, collaboration and impact were examined. Result: 521 articles were published in 21 Journals, of which 20 are international and 13 are within the first quartile (Q1), led by Clinical Oral Implants Research. There was a prevalence of Spanish language publications, without collaboration, and in Revista Cubana de Estomatología. The Cuban scientific leadership significantly diminishes in the journals located in the highest visibility quartile (Q1) (p=0.0144). The high dependency of citation-based indicators, as well as international collaboration, in rela-tion to the journals' quartile, was confirmed. Conclusion: The national scientific output in first quartile journals that has the biggest influence on the scientific international community is dependent on international collaboration to reach high levels of visibility and impact, and the national scientific output is not still able to systematically generate research that impacts in a significant way the scientific international community.